Republic of Korea : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This note is on Korea's transition to a knowledge-based economy, the prospects and challenges ahead, and the development of its financial sector. Assessment of recent government initiatives to develop capital markets has been presented. The note discusses restrictions on Chaebol ownership of Korean banks and strategy for restructuring the small and medium-sized enterprise sector in Korea. This note describes the key fiscal challenges and discusses possible ways to address them, arguing that there is already a great need to start taking remedial action.